2017
DOI: 10.1016/j.otsr.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survivorship of the Corail™ standard stem

Abstract: Level IV (retrospective study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 16 publications
1
39
1
2
Order By: Relevance
“…The results of this study group are comparable to to previous published cohorts as shown by Delauny, giving survival rates of 99% for aseptic loosening after a timespan of 7 to 8 years [1]. Other stems with excellent long term results in younger patients such as CLS Spotorno (72.8 any reason after 23.8 years) [10,12,11], Bicontact (93.57% at 12 years) [6,5] and Corail (95% at 12 years) [8,9] show good results up to 24 years of follow-up, but none of the mentioned cohorts give results for a period up to the end of the third decade as we do. Published data does sometimes not focus on the long-term problems such as wear of early polyethylene liners, therefore the reason for aseptic loosenings stays unclear in most cases.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study group are comparable to to previous published cohorts as shown by Delauny, giving survival rates of 99% for aseptic loosening after a timespan of 7 to 8 years [1]. Other stems with excellent long term results in younger patients such as CLS Spotorno (72.8 any reason after 23.8 years) [10,12,11], Bicontact (93.57% at 12 years) [6,5] and Corail (95% at 12 years) [8,9] show good results up to 24 years of follow-up, but none of the mentioned cohorts give results for a period up to the end of the third decade as we do. Published data does sometimes not focus on the long-term problems such as wear of early polyethylene liners, therefore the reason for aseptic loosenings stays unclear in most cases.…”
Section: Discussionsupporting
confidence: 84%
“…Some studies describe longterm results up to 20 years [4]. Other well established stem systems are reported to have excellent long term results such as Bicontact [5,6], Taperloc [7], Corail [8,9], CLS [10][11][12] as well as threaded cups such as T-TAP ST [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other stems with excellent long term results in younger patients such as CLS Spotorno (72.8 any reason after 23.8 years) [10,12,11], Bicontact (93.57% at 12 years) [6,5] and Corail (95% at 12 years) [8,9] show good results up to 24 years of follow-up, but none of the mentioned cohorts give results for a period up to the end of the third decade as we do. Published data does sometimes not focus on the long-term problems such as wear of early polyethylene liners, therefore the reason for aseptic loosenings stays unclear in most cases.…”
Section: Discussionmentioning
confidence: 44%
“…Many published reports have described the long-term survivorship of implants, including good results in cases of total hip and total knee arthroplasty and anatomical shoulder replacement [ [5] , [6] , [7] ]. However, implant failures such as fractures, loosening, and infection have also been reported [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%